Effectiveness of advertisement on consumer buying behaviour: A case of Moshi municipal-Kilimanjaro - Bee, Filomena Faustine (Mzumbe University, 2024)
Dissertation submitted to the School of Business as a partial fulfilment of the requirements for award of the Degree of Master of Business Administration in Corporate Management (MBA-CM) of Mzumbe University.